Biaya Distribusi Logistik dan Volume Penjualan pada Perusahaan Perkebunan Crude Palm Oil di Indonesia - Apriliana, Titik Susilowati; Nofrisel, Nofrisel; Abidin, Zaenal; Indrawan, Rully; Soekirman, Atong (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The study aims to find out the contribution of distribution costs using Franko system and Cost Insurance Freight to sales volume mediated by the selling price in PT Minamas Plantations. Some of the problems in the research were the low level of efficiency to produce product volumes including Crude Palm Oil and the delay in loading or unloading using Cost Insurance Freight (CIF) distribution system resulted in demurrage costs. The statistical method used to test the hypothesis was Partial Least Square with Smart PLS-3 program. The sample was taken from 31 months data of distribution costs using Franko system and Cost Insurance Freight. The conclusion of the research is the Crude Palm Oil selling price is able to mediate the distribution costs using Franko system and CIF of its sales volume in PT Minamas Plantations. The key finding, based on the statistical results, shows that the biggest influence is the distribution cost variable based on Cost Insurance Freight system.